THE importance of microRNAs in Endocarditis Associated with Staphylococcus aureus - Yasir, Alaa; Ghaidaa Gihadi Mohammed (University of Thi-Qar Journal of Science, 2024)
Abstract— Prosthetic valve endocarditis is a rare microbial infection but a dangerous complication of cardiac valve replacement surgical treatment. This study aims to figure out the genotype of Staphylococcus aureus isolated from patients with PVE by multilocus sequence typing (MLST). The study included 117 patients who were diagnosed with prosthetic valve endocarditis during the period of January to September 2023 at Heart Center Hospital in Al-Nasiriya city, Iraq. From each patient, blood (5 ml) were collected and cultured on differential and selective media, to isolate Staphylococcus aureus that identified according to standard methods and then confirmed the identification by using the API-20 Staph system and by PCR using mecA gene. . As well as detection of microRNA -15 and microRNA-24 as a biomarker of Staphylococcus aureus Prosthetic valve endocarditis the detection the levels of microRNA -15 and microRNA-24 by Real-Time PCR. The results showed that out of (117) studied specimens, there was 25 (11.52%) of them had given growth, while only 21 (84.00%) of them were gram-positive bacteria, and only 14 (66.67%) of them were identified as Staphylococcus aureus, and most of them were MRSA infections with a rate 11 (78.57%), which have been more confirmed by detection of mecA gene. The results of miR-15 and miR-24 expression showed the mean fold change of microR-15 level in patients was lower than in control groups (3.89) versus (4.97). Whereas the mean fold change of miR-24 level in patients was (19.11), which was higher than that of control groups (12.92).